Validating the Inventory of School Motivation with Mainland Chinese Students - Li, Feifei; Kauffman, Yashu; Thomas, Michael; Dempsey, Michael S.; Wang, Shiyuan; Kauffman, Douglas F. (Frontiers in Education, 2017)
The purpose of this study was to validate the Inventory of School Motivation (Mainland China), which was developed specifically for use with Mainland Chinese students. Development of the instrument was grounded in Personal Investment theory and built on the Inventory of School Motivation instrument, which has been shown to accurately tap the achievement goal constructs hypothesized by the theory. Our data analysis indicated that the subscales in our instrument do represent dimensions associated with achievement goals: task, effort, competition, social power, affiliation, social concern, praise, and token. Participants were 458 undergraduates from five universities in eastern China. A series of nested confirmatory factor analyses supported a multidimensional school motivation structure. The results indicated both convergent and concurrent validity for the instrument with Mainland students. Relationships were found between Inventory of School Motivation goal constructs and global motivation goals, family-oriented goals, self-concepts, and learning approaches. Our findings support that Mainland Chinese students’ achievement goal orientation is consistent with that found in other cultures, suggesting that the instrument and the theory that informs it may further cross-cultural research in this area. At the same time, though, our findings show that Mainland students endorse some goal orientations differently from other groups, suggesting an inventory instrument specific to Mainland China is both important and necessary.